2021
DOI: 10.1186/s13068-021-02039-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of the oleaginous yeast Yarrowia lipolytica PO1f for production of erythritol from glycerol

Abstract: Background Sugar alcohols are widely used as low-calorie sweeteners in the food and pharmaceutical industries. They can also be transformed into platform chemicals. Yarrowia lipolytica, an oleaginous yeast, is a promising host for producing many sugar alcohols. In this work, we tested whether heterologous expression of a recently identified sugar alcohol phosphatase (PYP) from Saccharomyces cerevisiae would increase sugar alcohol production in Y. lipolytica. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“… Mirończuk et al (2017) functionally overexpressed TKL1 , TAL1 , ZWF1, and GND1 , among which TKL1 overexpression increased erythritol production by 2 times. However, Jagtap et al (2021) did not find that overexpression of the TKL1 gene in the Y. lipolytica PO1f strain increased erythritol, possibly because the Y. lipolytica PO1f strain is an uracil and leucine auxotrophic strain, which somehow limits erythritol production.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“… Mirończuk et al (2017) functionally overexpressed TKL1 , TAL1 , ZWF1, and GND1 , among which TKL1 overexpression increased erythritol production by 2 times. However, Jagtap et al (2021) did not find that overexpression of the TKL1 gene in the Y. lipolytica PO1f strain increased erythritol, possibly because the Y. lipolytica PO1f strain is an uracil and leucine auxotrophic strain, which somehow limits erythritol production.…”
Section: Discussionmentioning
confidence: 80%
“… Mirończuk et al (2014) found that the mutant Y. lipolytica Wratislavia K1 obtained by acetate-negative mutation was suitable for producing large amounts of erythritol. In addition, a few records of Y. lipolytica producing erythritol from glycerol have been reported ( Rakicka et al, 2016b ; Carly et al, 2017 ; Mirończuk et al, 2019 ; Bilal et al, 2020 ; Mawire et al, 2020 ; Jagtap et al, 2021 ). Crude glycerol is the principal by-product of the manufacturing of biodiesel, an emerging alternative and sustainable fuel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intracellular metabolites become diluted in the more voluminous extracellular medium, adding to significant variability in intracellular metabolite quantitation due to the presence of interfering extracellular metabolites and concentrated media components ( Faijes et al, 2007 ). Fast filtration has also been used to separate microbial cells from cell culture medium prior to quenching through liquid nitrogen immersion or cold/hot solvent ( Castaño-Cerezo et al, 2019 ; Wordofa et al, 2017 ; Kim et al, 2013 ; Jagtap et al, 2021 ). Even though this method overcomes the issue of intracellular metabolite leakage, the quenching of cell metabolism is not immediate due to the time required for the filtration process.…”
Section: Generation Of Metabolomics Datamentioning
confidence: 99%
“…The genomic DNA and total RNA of Z. rouxii NRRL Y-64007 were extracted using the Dr. GenTLE (from yeast) high recovery kit (TaKaRa Bio Inc., Shiga, Japan) and the RNeasy minikit (Qiagen, Hilden, Germany), respectively ( 11 , 12 ).…”
Section: Announcementmentioning
confidence: 99%